Analisis Pengendalian Kualitas dengan Metode DMAIC pada Perusahaan Kertas Karton - Sihombing, Rustam; Arifin, Moh. Mawan; Annisa, Rhaina (Universitas Teuku Umar, 2024)
The very rapid development of the industrial world will have an impact on competitive competition between one company and another. Increasingly tight competition between companies means that companies must continue to improve the quality of the products they produce in order to produce good quality. This research aims to identify the causes of paper product defects in production units and analyze and improve product quality using the Six Sigma method. Data was collected through field observations and interviews, then analyzed using DMAIC (Define, Measure, Analyze, Improve, Control) analysis, a framework that aims to improve quality and efficiency by identifying and eliminating the causes of defects or problems in business processes. The analysis results show that the current sigma level is 2.907 with the largest product defect being color defects with a percentage of 37.77% caused by human, machine, material, method and environmental factors. The repair stage is carried out using FMEA (Failure Mode and Effects Analysis) to identify potential problems and determine recommendations for improvement. Recommendations for improvement activities in quality control emphasize regular monitoring and repair of machines as a guide for operators to maintain consistency in carrying out work procedures, increasing the frequency of regular machine inspections, especially for machines that frequently result in defective products, routine replacement of spare parts and repairs. environmental conditions to be carried out in accordance with the initial design of the equipment. And it is hoped that the activities carried out in improving quality control, emphasizing regular supervision and repair of machines, are expected to be able to increase productivity and quality of work produced and can increase profits for the company.